2023
DOI: 10.4236/ojbm.2023.111007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Employee Engagement on Employee Performance in Ghana’s MSMEs Sector during COVID-19: The Moderating Role of Job Resources

Abstract: Small, micro, and medium enterprises (MSMEs) across the globe were largely affected by the COVID-19 pandemic, which has plunged the business world into a serious crisis. However, Employee Engagement (EE) has been labeled as an essential nutrient that organizations need in order to survive in these turbulent times. This study was to examine the effect of EE on Employee Performance during the COVID-19 pandemic and how job resources moderate this relationship. The study used a sample size of 395 respondents who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Moreover, this study demonstrated that MSMEs frequently encounter difficulties in maintaining skilled workforce. Nkansah et al (2023) revealed a positive relationship between employee engagement and employee performance while also highlighted the major impact of job resources on employee engagement.…”
Section: Employee Engagement and Motivation In Msmesmentioning
confidence: 92%
“…Moreover, this study demonstrated that MSMEs frequently encounter difficulties in maintaining skilled workforce. Nkansah et al (2023) revealed a positive relationship between employee engagement and employee performance while also highlighted the major impact of job resources on employee engagement.…”
Section: Employee Engagement and Motivation In Msmesmentioning
confidence: 92%
“…Employee motivation and involvement have a significant influence on MSME performance ( (Nkansah et al, 2023); ((Bustasar et al, 2019)). Research has shown that motivation, both monetary and non-monetary, is a key factor in organizational performance and there is a significant relationship between motivation and employee performance (Aglina Ulfah & Nilasari, 2023).…”
Section: ) Employee Motivation and Engagementmentioning
confidence: 99%
“…Additionally, gamification techniques can foster a healthy feeling of competition among employees, which can foster a work climate that prioritizes continuous improvement and, as a result, raise profits (Dutton, 2023). According to (Nkansah et al, 2023), a personal resources intervention would enhance employee engagement and employee performance.…”
Section: Unlocking Revenue Potential: the Impact Of Gamification In E...mentioning
confidence: 99%